2020
DOI: 10.1002/jsfa.10941
|View full text |Cite
|
Sign up to set email alerts
|

Effects of superfine grinding using ball‐milling on the physical properties, chemical composition, and antioxidant properties of Quercus salicina (Blume) leaf powders

Abstract: BACKGROUND: Quercus salicina (Blume) leaves are traditionally used as folk medicine in some Asian countries. The aim of this study was to evaluate the effects of ball milling for different periods (0, 6, 12, 18, and 24 h) on the physicochemical properties of superfine Quercus salicina (Blume) leaf (QSL) powders. RESULTS:The particle sizes, water-holding capacity, angle of repose, and redness of the superfine QSL powder decreased with increasing ball-milling times, whereas the water solubility index, bulk densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 46 publications
3
8
0
Order By: Relevance
“…This could be attributed to higher surface adhesion and adsorption properties of the superne powder particles, as well as the decreased uidity caused by their adsorption and agglomeration characteristics. 38 These ndings are consistent with the observations of Hong et al, 39 who reported that powder uidity typically declines in conjunction with decreased particle size due to polymer formation. 40 Contrarily, Wang 41 used airow comminution for the superne grinding of Lentinus edodes powder processed via ordinary crushing.…”
Section: Color Uidity and Lling Propertiessupporting
confidence: 86%
“…This could be attributed to higher surface adhesion and adsorption properties of the superne powder particles, as well as the decreased uidity caused by their adsorption and agglomeration characteristics. 38 These ndings are consistent with the observations of Hong et al, 39 who reported that powder uidity typically declines in conjunction with decreased particle size due to polymer formation. 40 Contrarily, Wang 41 used airow comminution for the superne grinding of Lentinus edodes powder processed via ordinary crushing.…”
Section: Color Uidity and Lling Propertiessupporting
confidence: 86%
“…It was significantly (P < 0.05) reduced from 70.36º to 60.25º with decreasing particle size, demonstrating that the MOS particles became flowable. Similar results were also reported for Quercus salicina (Blume) leaf powders (Hong et al, 2020) and hard white winter wheat (Triticum aestivm L.) bran powders (He et al, 2018). Therefore, the fluidity of the MOS powders could be significantly improved by sieve-based mechanical grinding.…”
Section: Angle Of Reposesupporting
confidence: 80%
“…After ball milling for 24 h, the content of free phenols and free flavonoids was high, 98.04 mg gallic acid equivalents (GAE)/g and 16.37 mg catechin equivalents (CE)/g, respectively. [20] In contrast, the total phenols content of QS leaves powder was 85.20 mg GAE/g when extracted at room temperature for 2 h. When examining the relationship between extraction temperature, extraction time, and total phenols and total flavonoids, the total phenols in QS leaves extract was found to be 553.11 -692.67 μg GAE/g. At extraction temperature of 70 °C, the total phenols content was positively correlated with time.…”
Section: Determination Of Total Phenols and Total Flavonoids Contentmentioning
confidence: 91%
“…[9] In the DPPH test, ABTS test, iron reduction antioxidant capacity (FRAP) test, and H 2 O 2 removal test of QS ultra-fine leaves powder, ball milling time was positively correlated with free phenol content and negatively correlated with phenols bound to the cell wall. [20] There is only one article about the antioxidant activity of QS stems, which is the study of its methanol extract. The study included QS stems extracts from five various of solvents, such as CHCl 3 , H 2 O and CH 3 OH (30, 60, 100 %), the free radical scavenging activity was measured by the DPPH method, and the anti-lipid peroxidation effect on human low-density lipoprotein was measured by TBARS method.…”
Section: Antioxidant Activity and Action Mechanismmentioning
confidence: 99%